Gene and genotype frequencies of immunoglobulin-like natural killer cell receptors in the population of Samara region - D. Yu. Klyuchnikov; Yu. Yu. Teterina; O. V. Tyumina; I. L. Davydkin (Онкогематология)
Background. The using of killer-cell immunoglobulin-like receptor (KIR) composition data is of increasing interest in clinical practice to select an optimal donor for allogeneic hematopoietic stem cell transplantation for treatment of hematologic malignancies to reduce graft versus host disease and the risk of relapse. It is also of interest to study the frequencies of KIR genes and genotypes in different populations. For the Russian Federation, KIR gene and genotype frequencies have been described for only a few relatively small samples and have not been fully studied. The study of KIR gene and genotype frequencies has not been conducted for the Samara region population to date.Aim. To study the frequencies of KIR genes and genotypes in the population of Samara region and to compare the data with previously described Russian populations.Materials and methods. To study the frequencies of KIR genes and genotypes, molecular genetic typing of 142 CBUs from the public cord blood bank of the Samara Regional Medical Centre “Dynasty” was performed. Molecular genetic typing of KIR genes was performed by polymerase chain reaction with sequence-specific primers with subsequent visualization of products in agarose gel. 16 KIR genes and pseudogenes were analyzed: 2DL1, 2DL2, 2DL3, 3DL1, 3DL2, 2DS1, 2DS2, 2DS3, 2DS4, 2DS5, 3DS1, 2DP1, 3DL3, 2DL4, 2DL5, 3DP1. KIR gene frequencies were determined by direct counting. Genotypes were determined using Allele Frequencies database. A determination B-content group was performed using the Donor KIR B-content group calculator. Statistical analysis was performed using the χ2 test.Results. The highest frequency of KIR inhibitory genes was found for KIR2DL1 (98.6 %), KIR3DL1 (98.6 %), KIR2DL3 (96.5 %), KIR2DL5 (46.5 %), and KIR2DL2 (34.5 %). The most frequent among the activating receptor genes was KIR2DS4 (89.4 %), the frequencies of other KIR activating genes were KIR2DS2 – 45.1 %, KIR2DS1 – 35.9 %, KIR2DS3  33.8 %, and KIR2DS5 – 26.1 %. Comparative analysis of KIR gene frequencies in the population of Samara region and other Russian populations revealed certain differences. Significant differences in the frequencies of occurrence were found for KIR2DL3, KIR2DS4, KIR2DL2, KIR2DL5, KIR2DS3, KIR2DS5, as well as KIR2DP1 and KIR3DP1. Examination of 142 samples revealed 45 different genotypes: AA genotypes were detected in 30 % and Bx genotypes in 70 % of cases. AA genotype ID195 with a frequency of 5.6 % was detected, which has not been previously described in Russian populations. Among the Samara region population sample, only 3.5 % had the “best” status, 20.4 % had the “better” status, and 76.1 % had the “neutral” status of the B-content.Conclusion. The results obtained in this sample on the frequencies of KIR genes and genotypes differ from the previously published data for the Russian Federation. Of interest is the finding of a greater diversity of genotypes among a rather small study group, the detection of an atypical ID195 genotype, and the difference in the representation of B-content groups. The analysis of KIR genotypes in the population of Samara region can be used in the selection of optimal CBU and hematopoietic cell/bone marrow donors in addition to HLA typing. Studying the frequency distribution of KIR and HLA genes and genotypes can play a role in the study of fundamental aspects of human immunology and population genetics.